Cuneiform Texts from Babylonian Tablets in the British Museum. Part XLVI. Babylonian Literary Texts - Lambert, W. G. (1965)
nos. 1-15: Epic of Atraḫasis; nos. 16-35: Gilgamesh Epic; nos. 36-42: Zû/Anzû Epic; nos. 45-50: Historiographical Texts; nos. 51-55: Specimens of Babylonian speculation and erudition.